Anterior cervical discectomy and fusion surgery versus total disc replacement: A comparative study with minimum of 10-year follow-up. Issue 1 (December 2017) - Yang, Si-Dong; Zhu, Yan-Bo; Yan, Suo-Zhou; Di, Jun; Yang, Da-Long; Ding, Wen-Yuan
Abstract Based on long-term follow-ups, this study was designed to investigate the incidence and risk factors for postoperative adjacent segment degeneration (ASD) after anterior cervical discectomy and fusion (ACDF) or total disc replacement (TDR) in treating cervical degenerative diseases. Between January 2000 and December 2005, 108 cases undergoing ACDF and 78 undergoing TDR, were enrolled into this study. All medical records were retrospectively collected. Every patient was followed up at least 10 years. Outcome assessment included visual analogue scale (VAS) score, Neck Disability Index (NDI) score, Japanese Orthopaedic Association (JOA) score, and radiographic parameters. Consequently, thirty-eight (35.2%) of 108 cases suffered from ASD in ACDF group, and 26 (33.3%) of 78 cases in TDR group. There was no statistical difference between the two groups regarding ASD incidence, VAS/NDI/JOA score, recovery rate. Logistic regression analysis showed that age (OR = 2.86, 95% CI, 1.58–4.14) and preoperative segmental lordosis (OR = 1.90, 95% CI, 1.05–3.20) were risk factors associated with increased odds of ASD regardless of surgical procedures. On the other hand, preoperative overall lordosis (OR = 0.54, 95% CI, 0.26–0.82) was most likely protective. In conclusion, advanced age and preoperative segmental lordosis were identified as risk factors for postoperative ASD, while preoperative overall lordosis proves to be a protective factor.